2020
DOI: 10.1177/1362361320908096
|View full text |Cite
|
Sign up to set email alerts
|

Contextual determinants of parental reflective functioning: Children with autism versus their typically developing siblings

Abstract: Parental reflective functioning is defined as holding in mind one’s child’s thoughts, feelings, beliefs, and intentions and reflecting on how these mental states may be affecting the child’s behavior. Although parental reflective functioning is often treated as a stable feature of the parent, there is growing appreciation that it may be shaped by the context in which the parent is operating. In this study, we examined parental reflective functioning using the Parental Developmental Interview when parents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…A second possibility is that parents faced with the puzzle posed by their child’s restricted communication try harder to understand them. Consistent with this idea a study by Enav et al (2020) suggests that parents compensate by developing higher levels of mentalisation (reflective functioning) in relation to their child with autism as opposed to their neuro-typical child. In contrast, Kirk and Sharma (2017) suggest that parents have similar levels of mentalisation towards their children but hold more negative emotionally toned descriptions of their child with autism.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…A second possibility is that parents faced with the puzzle posed by their child’s restricted communication try harder to understand them. Consistent with this idea a study by Enav et al (2020) suggests that parents compensate by developing higher levels of mentalisation (reflective functioning) in relation to their child with autism as opposed to their neuro-typical child. In contrast, Kirk and Sharma (2017) suggest that parents have similar levels of mentalisation towards their children but hold more negative emotionally toned descriptions of their child with autism.…”
Section: Introductionmentioning
confidence: 76%
“…In contrast, Kirk and Sharma (2017) suggest that parents have similar levels of mentalisation towards their children but hold more negative emotionally toned descriptions of their child with autism. In short, these recent studies suggest a somewhat contradictory picture and use different ways of measuring mentalisation with only Enav et al (2020) using the more sophisticated measure of reflecting functioning offered by the Parent Development Interview (PDI: Aber et al, 1985).…”
Section: Introductionmentioning
confidence: 99%
“…But when stress is too great, automatic modes prevail. Along similar lines, Enav and colleagues (2020) compared the levels of PRF on the PDI when mothers were describing their child with autism with that of their description of typically developing siblings. In a sample of 30 mothers with one autistic and at least one typically developing sibling, they found that the levels of PRF were consistently higher when mothers were speaking about the child with autism ( p < .001).…”
Section: Resultsmentioning
confidence: 99%